Advertisement Remove all ads

Find the inverse of the following matrix using elementary operations. "A" = (1,2,-2), (-1,3,0),(0,-2,1) - Mathematics

Sum

Find the inverse of the following matrix using elementary operations.

`"A" = [(1,2,-2), (-1,3,0),(0,-2,1)]`

Advertisement Remove all ads

Solution

We know that
A =I A
or, `[(1,2,-2),(-1,3,0),(0,-2,1)] =[(1,0,0),(0,1,0),(0,0,1)]"A"`

⇒ `[(1,2,-2),(0,5,-2),(0,-2,1)]=[(1,0,0),(1,1,0),(0,0,1)]"A"` ...[Applying R2 → R2 + R1]

⇒ `[(1,2,-2),(0,1,0),(0,-2,1)]=[(1,0,0),(1,1,2),(0,0,1)]"A"` ...[Applying R2 → R2 + 2R3]

⇒`[(1,0,-2),(0,1,0),(0,0,1)]=[(-1,-2,-4),(1,1,2),(2,2,5)]"A"
`...[Applying R1 → R1 + (-2)R2,R3 → R3 +2R2 ]

⇒`[(1,0,0),(0,1,0),(0,0,1)]=[(3,2,6),(1,1,2),(2,2,5)]"A"` ...[Applying R1→ R1+2R3 ]

Hence, `"A"^(-1) = [(3,2,6),(1,1,2),(2,2,5)]`

Concept: Inverse of a Matrix - Inverse of a Nonsingular Matrix by Elementary Transformation
  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×